Al-Tamadhhub al-Fiqhī wa-Ḥifẓ al-Ḍarūriyyāt al-Khams bayna al-Waḥdah wa-al-Taʿaddud: Dirāsah fī Ikhtilāfāt al-Fuqahāʾ - Yusuf Usman; Bishir Salis Idris (Al-Zahra : Journal for Islamic and Arabic Studies, 2025)
This study examines adherence to juridical madhhab and its role in preserving the five essential objectives (al-ḍarūriyyāt al-khams) of Islamic law between unity and plurality, through an analytical study of juristic disagreement. It addresses the prevailing assumption that madhhab-based reasoning constitutes an obstacle to legal reform and promotes doctrinal rigidity. The study argues instead that madhhabism represents a disciplined methodological framework that historically regulated legal disagreement, structured juristic reasoning, and safeguarded the higher objectives (maqāṣid) of the Sharīʿa from fragmentation and arbitrary interpretation. Employing an inductive-analytical method combined with comparative analysis across the four Sunni legal schools, the study draws on classical works of fiqh, uṣūl al-fiqh, and maqāṣid al-sharīʿa. Selected cases related to the preservation of religion, life, intellect, lineage, and property demonstrate that juristic plurality does not signify divergence in legal objectives or a violation of foundational principles. Rather, it reflects diverse interpretive mechanisms aimed at realizing shared higher goals within varying historical and social contexts. The study concludes that adherence to madhhab remains a normative and practical mechanism for balancing unity at the level of objectives with plurality at the level of legal interpretation, reaffirming its relevance in contemporary Islamic legal discourse.